Pengaruh Promosi Terhadap Pembuatan Dispensasi Izin Mendirikan Bangunan Pada Badan Penanaman Modal Dan Perizinan (BPMP) Di Bandar Lampung - Nur'aeni NUR'AENI; Harada Yusneli (Jurnal Manajemen dan Bisnis, 2012)
Building permit dispensation ( D - IMB ) is a program of the City of Dublin to provide relief to the people in order to have a building permit under the built in 2011 . Order for the public to know the program , the Board of Investment and Licensing ( CEW ) Bandar Lampung society promotion in hopes of making the IMB will file through the D - IMB . The purpose of this study to determine whether a significant effect on the promotion of the manufacture of D - IMB amount in CEW Bandar Lampung . This study used a descriptive method with 44 respondents that were collected Random Sample Sampling . From the qualitative analysis of the results obtained : statements relating to the promotion of respondents who entered higher by 15.9% category , the category was 63.6% , and 20.4% lower category , while statements relating to the manufacture of building permit dispensation incoming category of high by 36.4% , 56.8 % moderate category , and the category of low 6.8 % . It can be concluded that the positive effect on the promotion of the manufacture of D - IMB . From the quantitative analysis with SPSS 20 values obtained R2 = 63.8 % , which means the amount of D - IMB -making is influenced by the Promotion 63.8 % and the remaining 36.2 % is influenced by other variables not examined . ρ - value < α is 0.000 < 0.05 , then Ho is rejected and Ha accepted . It can be concluded that the hypothesis promotion significant effect on the number of building permit dispensation of making the Board of Investment and Licensing Bandar Lampung , is acceptable .